Observation of anomalous impurity transport during low-density experiments in W7-X with laser blow-off injections of iron. (7th February 2019) - Geiger, B.; Wegner, Th.; Beidler, C.D.; Burhenn, R.; Buttenschön, B.; Dux, R.; Langenberg, A.; Pablant, N.A.; Pütterich, T.; Turkin, Y.; Windisch, T.; Winters, V.; et al.
Abstract: The transport of heavy impurities has been investigated at the Wendelstein 7-X stellarator during core electron root confinement (CERC) experiments. Iron atoms were injected via the laser blow-off technique and analyzed by VUV and x-ray spectrometers. The injected amount of iron does not change the global plasma parameters but yields strong enough line radiation for detailed studies based on the impurity transport code STRAHL. The latter is supplied with neo-classical diffusion and convection profiles from the drift kinetic equation solver (DKES) and has been embedded into a least-squares fit that searches for additional anomalous diffusion and convection profiles, required to explain the measurements. While the resulting convection velocities agree within uncertainties with neo-classical theory, the anomalous diffusion profile exhibits values more than two orders of magnitude larger than the neo-classical one. This significant level of anomalous transport is possibly explained by turbulence. The high ratio and flat density profile present during the experiment yield low thresholds for temperature gradient driven modes that are expected off-axis where the obtained diffusion profile peaks.